استخدام الباحثین بالجامعات السعودیة لمواقع التواصل الاجتماعى العلمیة : دراسة استکشافیة لموقعى بوابة البحث Researchgate وأکادیمیا Academia - د. ابراهیم حسن أبو الخیر (المجلة الدولية لعلوم المكتبات والمعلومات)
The Academic social networks are the latest means used by researchers and scientists use to communicate with each other. They are also used to access scientific information, such as articles and research available on them. The paper aims to finding out the extent of which scholars working at Saudi universities use these networks, specifically ResearchGate, and Academia, in the scholarly communication process. It also aims at knowing the extent of the scholars use of these two networks in promoting themselves, and the disseminating their scientific productions on the Internet.Thirty-three Saudi university were studied, twenty-five of them are governmental, and eight of them are private. King Saud University, King Abdulaziz University, King Fahd University of Petroleum and Minerals in Dhahran, and King Abdullah University of Science and Technology, are the highest most effective participating universities in both Academia and ResearchGate. The least participating universities in both networks, whether in terms of participating individuals, or posted research, are the relatively new and emerging universities. These universities do not have a large number of faculty members, researchers, or students. The highest participating departments in Academia and ResearchGate, are the natural sciences, and applied science departments. The least participating departments are the humanities and social sciences departments.The most covered subject areas in Academia, are science, health and social services, and engineering, construction and production industries, while the least subject areas covered were the services, unspecified programs, and education. The most covered subject areas in ResearchGate, are health and social services, science, and engineering, and construction & production industries, while the least subject areas covered were humanities, arts, social sciences, business, law, and the unspecified programs.